Grain boundary character distribution and its effect on corrosion of Ni–23Cr–16Mo superalloy. Issue 1 (2nd January 2017) - Shi, P.; Hu, R.; Zhang, T.; Yuan, L.; Li, J.
Abstract : Grain boundary character distribution (GBCD) of the Hastelloy C2000 alloy (Ni–23Cr–16Mo) and the effect of coincidence site lattice (CSL) grain boundaries on corrosion resistance were examined by electron backscattered diffraction and electrochemical experiments. Various deformation followed by annealing was applied to optimise the GBCD of the alloy. After grain boundary engineering (GBE) treatment, the proportion of CSL boundaries increased from 37.7% to 62.4% and the corrosion current density of the specimens decreased in NaCl solution. The results indicated that GBE treatment is responsible for preferable corrosion resistance due to the increase of the fraction of special low energy grain boundaries with perfect grain boundary atom arrangement after thermomechanical process.